Activate Reading Comprehension of Second Language Acquisition (SLA) By Applying Know-Want to Know-Learned (KWL) Strategy - Adieli Laoli (IJEE (Indonesian Journal of English Education), 2021)
ABSTRACTThe purpose of this research is to describe how students achieve their reading comprehension performance when they apply the KWL (Know, Want to Know, Learned) Strategy. KWL is a strategy that can better comprehend the content of material read by the students. Using this strategy can help the students read effectively and efficiently to build their comprehension. After analyzing the data, the finding shows that the KWL Strategy positively contributes to the students’ achievement in their reading comprehension. It can be seen from the progress of scores in each cycle that the students acquired. Other aspects that the students should have in applying this strategy, such as motivation and vocabulary mastery, play a vital role in classroom activities; besides, the serious attention of the teacher to use the procedures of KWL strategy is necessary. The result of this research is KWL strategy can increase the students' reading comprehension in Second Language Acquisition (SLA) subject by applying some modifications to the procedures. Considering the result from the research, the researcher recommends that the KWL strategy be continuously implemented in activating students’ reading comprehension.ABSTRAKTujuan dari penelitian ini adalah untuk mendeskripsikan bagaimana siswa mencapai pemahamannya ketika menerapkan Strategi KWL. KWL merupakan salah satu strategi yang dapat memberikan pemahaman yang lebih baik akan sebuah konten materi yang dibaca oleh siswa. Penggunaan strategi dapat membantu siswa membaca secara efektif dan efisien untuk membangun pemahaman. Hasil analisis data menunjukkan bahwa Strategi KWL memiliki kontribusi positif terhadap prestasi siswa dalam memahami bacaan SLA, hal ini dapat dilihat dari kemajuan akan nilai dalam pembelajaran yang diperoleh siswa. Aspek lain yang harus dimiliki siswa dalam menerapkan strategi ini, misalnya motivasi dan penguasaan kosakata memegang peranan yang sangat penting dalam kegiatan kelas, selain itu perhatian serius dari guru untuk menerapkan prosedur strategi KWL mutlak diperlukan. Hasil dari penelitian ini menunjukkan bahwa strategi KWL dapat meningkatkan pemahaman membaca siswa pada pelajaran SLA dengan penerapan beberapa modifikasi pada prosedurnya. Berdasarkan hasil penelitian tersebut, peneliti merekomendasikan strategi KWL untuk diimplementasikan secara berkelanjutan untuk meningkatkan pemahaman membaca siswa.